Biodiversity of certain invertebrates (Insecta, Molluska) of the Azat River gorge, Armenia and their bioecological features - V. S. Hovhannisyan; L. S. Mirumyan; R. G. Harutyunyan; A. A. Avetisyan; L. D. Harutyunova; A. S. Gasparyan; M. Z. Magomedova; P. D. Magomedova (Юг России: экология, развитие)
Aim.  The  aim  of  the  work  is  to  study  the  biodiversity of  certain invertebrates (Insecta,  Molluska) of  the  Azat River  gorge and their ecological and biological features.Material   and  Methods.  Invertebrates  collected in  the  Garni‐Goght‐ Geghard section of the Azat River gorge in the period from 2015 to 2021 served as study material.The work  was  carried out at  the  Scientific Center for  Zoology  and Hydroecology of the National Academy of Sciences of the Republic of Armenia. Our own collections have been used as material, as well as collections of insects and mollusks of the Institute of Zoology.Results. As a result of studies of the species composition of invertebrates of the Azat River gorge (Geghard, Goght, Garni) we found: 25 species of horseflies (Tabanidae: Diptera), 24 species of phytophagous gall midges (Cecidomyiidae: Diptera); 13  aphid species (Aphididae: Hymenoptera); 17  pyralid moth species (Crambidaе: Lepidoptera) from 5 subfamilies (Crambinae,  Evergestinae,   Pyraustinae,  Spilomerlinae,  Glaphyriinae); 19 species of mollusks (Molluska): 3 species of freshwater mollusks from 3 families (Physidae, Planorbidae, Ancylidae), 16  species of terraneous mollusks from 10 families (Succineidae, Vertiginidae, Orculidae, Pupillidae Valloniidae, Enidae, Vitrinidae, Endodontidae,  Limacidae, Helicida). The bioecological features of these insects and mollusks have been studied and distribution by biotopes, revealing changes in the species composition of some groups due to anthropogenic factors.Conclusion. As a result of the researches undertaken, a wide variety of invertebrates has been frevealed. They occupy all ecological niches and are found in all plant formations of the Azat River gorge. Most of the insect species are of economic importance. Research on invertebrates of the Azat river gorge is very promising. Works in this direction will be continued with the involvement of new research groups.